Unveiling Three Key Drivers of Employee Performance: The Self-Determination Theory Perspectives - Novarina, Wiwik (PT Global Digital Sains Tekno, 2024)
Understanding the factors influencing employee performance is crucial for enhancing organizational effectiveness and achieving business goals. This study aimed to analyze the significance of the influence of work motivation, job satisfaction, and work discipline on employee performance at F&B Cafe in Surabaya. The method used in this research is descriptive with a quantitative approach. From the research results, it can be concluded that work motivation significantly and positively affects employee performance at F&B Cafe in Surabaya. Using the self-determination theory, an employee’s good performance can improve organizational performance in order to achieve company goals. Job satisfaction significantly affects employee performance at F&B Cafe in Surabaya. This shows that the higher the employee's job satisfaction, the higher the employee's performance. Work Discipline does not significantly affect employee performance at F&B Cafe in Surabaya. Without work discipline from employees, it will be difficult for companies to get optimal results because employee performance is not good. Good morale will emerge from discipline because it is this discipline that shapes the character of employees. These results underscore the importance of focusing on work motivation and job satisfaction to drive employee performance and ultimately support the company's overall success.